Datuk M. Asojan receives Lifelong Learning Professional Award - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 6 August 2022 – Despite being busy with his essential duties as Vice President of Malaysian Indian Congress (MIC) and Unit Manager, the situation was not a hindrance for this Durian Tunggal-born to achieve success.